Plankton Diversity in Aek Rao River Gunung Tua - Rosenta Purba, Ika; Harahap, Arman (International Journal of Science, Technology & Management, 2022)
The purpose of this study was to determine the index of plankton diversity in the Aek Rao River, Gunung Tua. The research was carried out from April to May 2022 in the Aek Rao River, Gunung Tua. The sampling method used purposive random sampling which consisted of 3 observation stations, namely station 1 upstream, station 2 for residential areas and station 3 for densely populated areas. The results showed that the composition of plankton in the Aek Rao River, Gunung Tua consisted of 3 classes of phytoplankton, namely Bacillariophyceae, Chlorophyceae and Cyanophyceae, while the zooplankton class consisted of 4 classes, namely Mastigophora, Monogononta, Crustacea and Ciliophora. The highest diversity index in phytoplankton was obtained at station 1 of the sand mining area with a value of 1, 39 which indicates that the level of diversity is in the medium category. In zooplankton the highest diversity index was found at station 3 with a value of 0.33 which indicated that the level of diversity was included in the low category. While the highest dominance index for phytoplankton was found at station 3 in densely populated areas with a value of 0.43 while zooplankton was found at station 1 in a sand mining area with a value of 0.00563, both values ??indicated that there was no dominant plankton genus in that area.